Предмет: Химия,
автор: Надюха352
. FeSO4 + NaClO3 + NaOH
Ответы
Автор ответа:
0
FeSO4
+ NaClO3 + NaOH → Fe(OH)3 + NaCl
6FeSO4 + NaClO3 + 12NaOH → 6Fe(OH)3 + NaCl + 6Na2SO4
6FeSO4 + NaClO3 + 12NaOH + 3H2O = 6Fe(OH)3 + NaCl + 6Na2SO4
6FeSO4 + NaClO3 + 12NaOH → 6Fe(OH)3 + NaCl + 6Na2SO4
6FeSO4 + NaClO3 + 12NaOH + 3H2O = 6Fe(OH)3 + NaCl + 6Na2SO4
Похожие вопросы
Предмет: Литература,
автор: hozyainkotamoty
Предмет: Математика,
автор: milka678588
Предмет: Информатика,
автор: KataPlatonova
Предмет: Математика,
автор: vanhelsing132